Vector competence of Glossina austeni and G. brevipalpis and characterization of Trypanosoma congolense strains from northern KwaZulu-Natal, South Africa - Latif, Abdalla A. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.